Training on making e-books for teachers at SMP IT Insan Permata Bojonegoro with AI - Tauchid, Ahmad (Community Empowerment Journal, 2023)
This article discusses community service activities aimed at training teachers of SMP IT Insan Permata Bojonegoro in utilizing learning technology, especially in making e-books using AI. This training aims to improve teachers' understanding of e-book applications, create teaching materials that can be accessed by students without being constrained by time and place, and provide better material visualization alternatives. The teachers are divided into groups to create e-books with relevant subject matter, involving hands-on practice in the creation of e-books. The comprehensive reflection and evaluation stage is an important step to ensure that community service goals are maximally achieved and provide sustainable benefits for teachers at SMP IT Insan Permata. This training is expected to open up new opportunities for a more modern and inclusive learning approach, as well as increase teachers' active involvement and participation in the learning process.